Synthesis, characterization, and magnetochemical properties of two Mn4 clusters derived from 2-pyridinecarboxaldehyde Schiff base ligands. Issue 7 (3rd April 2017) - Tian, He; Qiao, Xin; Xie, Cheng-Zhi; Ouyang, Yan; Xu, Jingyuan
Abstract: Two tetranuclear manganese complexes, [Mn4 (L 1 )6 ](ClO4 )2 ⋅2.75H2 O (1 ) [HL 1 = 4-methyl-2-((pyridin-2-ylmethylene)amino)phenol] and [Mn4 (L 2 )4 (NO3 )3 (OH)]⋅pz⋅3H2 O (2 ) [HL 2 = (1 H -pyrazol-1-yl)(pyridin-2-yl)methanol, pz = pyrazole], have been synthesized and characterized by IR spectroscopy, elemental analysis, single-crystal X-ray diffraction, and magnetic measurements. The structural analysis revealed that the central manganese ion is linked with three apical manganese ions through six phenoxo-bridges creating a Mn4 O6 core for1 ;2 has a cubane-like topology with the Mn(II) ions and the deprotonated oxygens from L 2 alternatively occupying vertices. The magnetic studies indicated a weak ferromagnetic coupling interaction ( J = 0.48 ± 0.087 cm −1, g = 2.00, θ = −0.78 K) for1 and a weak antiferromagnetic spin-exchange interaction ( J 1 = −0.50 ± 0.075 cm −1, J 2 = −0.13 ± 0.082 cm −1, g = 1.98) between Mn(II) ions for2 . The magnetostructural correlations of the two Mn4 clusters have been discussed tentatively. Abstract :